Faktor penghindaran pajak perusahaan consumer non-cyclicals terdaftar di Bursa Efek Indonesia - Lestari, Anggi; Adi Indrawan, I Gede; Prananta Widya Sasana, Lodang (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This research aims to determine and analyze factors that can influence the occurrence of tax avoidance activities (CETR) carried out by non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2017-2021, such as capital intensity (CAIN) factors, institutional ownership. (INST) and executive character (RISK) either partially or simultaneously. The type of research used in this research is quantitative which is related to numbers or statistics and uses secondary data, namely coming from the annual reports of non-cyclical consumer companies listed on the Indonesia Stock Exchange for 2017-2021. The sampling technique in the research used a purposive sampling method with a total of 36 non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2017-2021 being the research sample. The analytical method used is descriptive statistical analysis and panel data regression analysis. The results of this research show that the capital intensity factor partially has no effect on tax avoidance, the institutional ownership factor partially has an effect on tax avoidance, and the executive character factor partially has an effect on tax avoidance. Meanwhile, capital intensity, institutional ownership and executive character together (simultaneously) influence tax avoidance.